Book Review. Issue 1 (1st March 2019) - Tassi, Nico
Abstract : Domesticating Democracy: The Politics of Conflict Resolution in Bolivia Susan Helen Ellison. Durham, NC: Duke University Press, 2018, ISBN: 9780822371083, 296 pp., Pb. $25.95. Reviewed by Nico Tassi